Biosensors: CRISPR/Cas13a‐Powered Electrochemical Microfluidic Biosensor for Nucleic Acid Amplification‐Free miRNA Diagnostics (Adv. Mater. 51/2019). Issue 51 (17th December 2019) - Bruch, Richard; Baaske, Julia; Chatelle, Claire; Meirich, Mailin; Madlener, Sibylle; Weber, Wilfried; Dincer, Can; Urban, Gerald Anton
Abstract : In article number 1905311, Can Dincer and co‐workers introduce the first CRISPR‐powered electrochemical microfluidic biosensor (CRISPR‐Biosensor), allowing nucleic‐acid‐amplification‐free detection of microRNAs in isolated serum samples. Upon recognition of its target, the activated Cas13a cleaves reporter RNAs in its surroundings, resulting in a decrease of the measured electrochemical signals. The CRISPR‐Biosensor offers a low‐cost, easily scalable, specific, and target amplification‐free (i.e., rapid and easy‐to‐use) tool for on‐site nucleic acid diagnostics.